Analysis Reinforcementscore of Characteristics Education “Kentrung Gas” Art in SMA 2 Bondowoso (George Herbert Mead's Theory of Interactionism Symbolic) - Kurniawan, F; Soepeno, B; Naim, Mohamad (Future Science / FSH-PH Publications, 2022)
Kentrung is the art of oral literature or the speaking of art (oral theater) accompanied by trebeng beats. Kentrung art is also found in Bondowoso, which has the characteristic of using the Madurese language as the language of instruction. Currently, kentrung art is popularized and often played by GAS (Grup Apresiasi Seni) Bondowoso. This study attempts to analyze Reinforcementscore of Characteristics Education of kentrung GAS art in SMA Negeri 2 Bondowoso which is studied through the interactionism symbolic theory of George Herbert Mead. This study uses a qualitative research method with the research location in GAS Bondowoso Studio and SMA 2 Bondowoso. The primary data sources in this study were the main informants, namely the puppeteers and kentrung performers of GAS Bondowoso and students of SMA 2 Bondowoso. Techniques of data collection in this study using interviews, observation and documentation. There are several uniqueness in the art form of kentrung GAS Bondowoso. First, the use of Madurese language in staging stories and reading rhymes of kentrung. Second, the number of personnel in the art of kentrung GAS Bondowoso is four to seven people. Third, the songs are sung using modern (popular) songs. Meanwhile, the structure of the Kentrung GAS Bondowoso art consists of several elements, namely elements of players, elements of stories, elements of costumes, elements of rhymes, and elements of instrumental music. Based on the research discussion, kentrung GAS Bondowoso from the perspective of interactionism symbolic theory describes 3 things. While Reinforcementscore of Characteristics Education of kentrung GAS art in SMAN 2 Bondowoso, it can be concluded that in the form and entire structure of kentrung GAS there are values for Reinforcement of Characteristics Education. Reinforcementscore of Characteristics Education are mostly found in the rhyme element of kentrung.